Experimental Investigations on Corrosion Model of Welded 6061 Aluminum Exposed in NaCl Solution - Asmara, Y.P.; Siregar, J.P.; Shah, L.H.; Tezara, C. (UMP, 2015)
Interpreting both each segmented region and multi-reactions for self-corrosion is important when investigating the corrosion rate in a welded structure. This research studied weld corrosion occurring on aluminum 6061 that can be considered from the electrical circuit concept. The research studied the corrosion process on two types of filler which were 4043 and 4047 filler. The electrical circuit model and corrosion test revealed that the heat affected zone (HAZ) region behaved as an anode and showed a higher corrosion rate for both types of filler. Samples using filler 4043 had a higher corrosion rate than filler 4047. Under an optical microscope, filler 4043 was seen to display inhomogeneous microstructures which relate to the corrosion process. Using the electrical model, study of the galvanic effects on each part of the weld regions showed realistic correlations to simulate the corrosion process in welded samples.